Optimizing In Situ Vaccination During Radiotherapy - Yasmin-Karim, Sayeda; Wood, Jana; Wirtz, Johanna; Moreau, Michele; Bih, Noella; Swanson, William; Muflam, Ashley; Ainsworth, Victoria; Ziberi, Bashkim; Ngwa, Wilfred (Frontiers in Oncology, 2021)
Effective in-situ cancer vaccines require both a means of tumor cell death and a source of adjuvant to activate local dendritic cells. Studies have shown that the use of radiotherapy (RT) to induce tumor cell death, and anti-CD40 to activate dendritic cells can result in in-situ vaccination in animal models. Here, investigations are carried out on potential strategies to enhance such in-situ vaccination. Strategies investigated include the use of smart immunogenic biomaterials (IBM) loaded with anti-CD40 in different tumor types including immunologically cold tumors like pancreatic and prostate tumors. The use of down-stream check-point inhibitors to further boost such in-situ vaccination is also examined. Results indicate the use of IBM to deliver the anti-CD40 significantly enhances the effectiveness of in-situ vaccination with anti-CD40 compared to direct injection in pancreatic and prostate cancers (p<0.001 and p<0.0001, respectively). This finding is consistent with significant increase in infiltration of antigen presenting cells in the treated tumor, and significant increase in the infiltration of CD8+ cytotoxic T lymphocyte into distant untreated tumors. Moreover, in-situ vaccination with IBM is consistently observed across different tumor types. Meanwhile, the addition of downstream immune check-point inhibitors further enhances overall survival when using the IBM approach. Overall, the findings highlight potential avenues for enhancing in-situ vaccination when combining radiotherapy with anti-CD40.